2013
DOI: 10.1371/journal.pone.0070944
|View full text |Cite
|
Sign up to set email alerts
|

Using the Electronic Medical Record to Identify Community-Acquired Pneumonia: Toward a Replicable Automated Strategy

Abstract: BackgroundTimely information about disease severity can be central to the detection and management of outbreaks of acute respiratory infections (ARI), including influenza. We asked if two resources: 1) free text, and 2) structured data from an electronic medical record (EMR) could complement each other to identify patients with pneumonia, an ARI severity landmark.MethodsA manual EMR review of 2747 outpatient ARI visits with associated chest imaging identified x-ray reports that could support the diagnosis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
1
27
0
2
Order By: Relevance
“…Finally, manual chart review to classify uncomplicated cases and related outcomes was laborious, and automated case identification is technologically plausible and should be explored. 39 In conclusion, this national VHA MUE found that patients with uncomplicated pneumonia were commonly prescribed antimicrobials for the duration of therapy in excess of guideline recommendations. Patients with uncomplicated pneumonia who received therapy duration consistent with guideline recommendations did not have significantly different all-cause readmission and death rates compared to patients receiving prolonged treatment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, manual chart review to classify uncomplicated cases and related outcomes was laborious, and automated case identification is technologically plausible and should be explored. 39 In conclusion, this national VHA MUE found that patients with uncomplicated pneumonia were commonly prescribed antimicrobials for the duration of therapy in excess of guideline recommendations. Patients with uncomplicated pneumonia who received therapy duration consistent with guideline recommendations did not have significantly different all-cause readmission and death rates compared to patients receiving prolonged treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Other work should include an in‐depth assessment of clinical outcomes related to treatment duration, investigation of provider rationale for prolonged treatment, and duration of antimicrobial therapy prescribed upon discharge for other common disease states. Finally, manual chart review to classify uncomplicated cases and related outcomes was laborious, and automated case identification is technologically plausible and should be explored …”
Section: Discussionmentioning
confidence: 99%
“…Information potentially useful to public health surveillance has long been extracted from the free text narrative of chief complaints [37][38][39][40][41], laboratory or imaging reports [37,38,[41][42][43][44], hospital discharge summaries [45,46] or outpatient clinical notes [19,47,48]. To date however, little is known about how information extracted from free text EMR fields should be combined with structured data to accelerate outbreak detection.…”
Section: Discussionmentioning
confidence: 99%
“…24 The authors are currently investigating the use of text-mining algorithms in order to extract unstructured data from the free text information documented in the EPR and convert this information to structured variables, such as previously described for community-acquired pneumonia by DeLisle et al Adding other types of HAI as well as employing a more complex set of definitions, such as those used by Shepard et al for catheter-associated UTI, may refine the HAIR algorithms and provide more informative data. 15,25 Although there are few commercial systems for electronic surveillance of HAI in general, none of these is available in Denmark. Commercial systems are expensive to procure and maintain; these costs may be avoided if existing databases within hospitals can be used as demonstrated in this study.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%